Effect of backstroke ledge on backstroke start technique for water entry - Sato, D.; Suito, H.; Yamashita, N.; Kusanagi, K.; Mizukami, T.; Takahashi, S. (Sports Biomechanics, 2024)
This study aimed to investigate how the use of a backstroke ledge (BSL) affects backstroke start performance in terms of flight distance and water entry posture in competitive backstroke swimmers. Ten male swimmers performed a maximum of 15 m in backstroke, starting with or without a BSL. Two 120 Hz and one 60 Hz video cameras were used to analyse the kinematic variables and angular momentum of the whole body. Using a BSL reduced the time to reach 5 and 15 m compared with not using a BSL (p < 0.04). Using a BSL heightened vertical position of the centre of mass (CM) at take-off, lengthened flight distance, and increased angular momentum (p < 0.02). Additionally, the lower limb entry angle was larger, and the hole entry posture angle was smaller with a BSL than without a BSL (p < 0.04). These results suggest that a high CM position at the start of the backstroke with a BSL increased the flight distance, and a large angular momentum enabled hole entry as well as improved the horizontal velocity after water entry. Hence, increases in flight distance and velocity after water entry were contributing factors in improving the start performance of the backstroke when using a BSL.